2016
DOI: 10.1017/psrm.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Issues and Their Fates in the US Congress

Abstract: Significant scholarship indicates that female legislators focus their attention on “women’s issues” to a greater extent than do male lawmakers. Drawing on over 40 years of bill sponsorship data from the US House of Representatives, we define women’s issues in terms of those sponsored at a greater rate by women in Congress. Our analysis reveals that most (but not all) of the classically considered women’s issues are indeed raised at an enhanced rate by congresswomen. We then track the fate of those issues. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…This mechanism reflects the politics of presence theory, or the idea that women in government are more inclined to legislate certain issues based on their experiences either as women in the labour force or as mothers ( Phillips, 1995 ). Previous political sociology research shows that women in government are more likely to advance public policies meant to support government spending in general, and women, children, and social welfare in particular ( Anzia & Berry, 2011 ; Bolzendahl & Brooks, 2007 ; Bratton & Ray, 2002 ; Volden, Wiseman, & Wittmer, 2016 ). Our study extends the implications of women in government to include improvements in population health (i.e., reductions in mortality rates).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism reflects the politics of presence theory, or the idea that women in government are more inclined to legislate certain issues based on their experiences either as women in the labour force or as mothers ( Phillips, 1995 ). Previous political sociology research shows that women in government are more likely to advance public policies meant to support government spending in general, and women, children, and social welfare in particular ( Anzia & Berry, 2011 ; Bolzendahl & Brooks, 2007 ; Bratton & Ray, 2002 ; Volden, Wiseman, & Wittmer, 2016 ). Our study extends the implications of women in government to include improvements in population health (i.e., reductions in mortality rates).…”
Section: Discussionmentioning
confidence: 99%
“…In the Senate, women make use of voter stereotypes about women to enhance their credibility on women's issues, but such stereotypes may also constrain women's efforts to lead on other, more "masculine" issues (Swers, 2013). Volden et al (2014) find that women's effort on behalf of women's issues (defined as issues to which women give the most legislative time and attention relative to men) turns out to be less successful than are men's efforts on behalf of their own interests. And of special relevance to our focus on meetings, the authors trace the institutional bias against women to what happens in committees -the settings Kathlene (1994) finds can be especially hostile to women.…”
Section: Women's Influence In American Political Institutionsmentioning
confidence: 94%
“…A long line of research in both state and national contexts reinforces this point by showing that female legislators tend to prioritize issues and interests that are distinct from those of their male colleagues, though the specific definitions and operationalizations of those issues has varied widely by study (Bratton, 2002;Bratton & Haynie, 1999;Burrell, 1994;Carroll, 1994;Walsh, 2002;Dodson & Carroll, 1991;Gerrity, Osborn, & Mendez, 2007;Htun & Weldon, 2010;Poggione, 2004;Reingold, 2000;Saint-Germain, 1989;Swers, 2002;Thomas, 1995;Thomas & Welch, 1991;Weldon, 2002Weldon, , 2011. Some define these distinctive "women's issues" as those where there is a large gender gap in attitudes; others look to issues championed by interest groups focused on women or issues where women of both parties tend to agree; still others focus on issues that are likely to be especially salient to women, such as the legislation focused on the needs of children, family, and women (for overviews, see Bratton, 2005;Reingold & Swers, 2011;Volden, Wiseman, & Wittmer, 2014). A more recent approach argues that women's issues should be defined "endogenously," by exploring the set of issues to which female members of Congress tend to devote more legislative attention than men (Reingold & Swers, 2011;Volden et al, 2014).…”
Section: Women's Influence In American Political Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Canadian study Ng and Muntaner () found that increases in women representation in government correlates with declines in male and female mortality rates. A potential mechanism for this population health influence may be that females are more likely to support increases in spending on social welfare programs (Bratton & Ray, ; Volden, Wiseman, & Wittmer, ).…”
Section: Discussionmentioning
confidence: 99%